Optimalisasi Prinsip Kehati-hatian dalam Penggunaan Artificial Intelligence oleh Notaris di Indonesia - Narwastuty, Dian; Yuniawaty, Yenny; Budioyo, Steven Savio (Jujurnal Publisher, 2026)
The rapid adoption of Artificial Intelligence (AI) in legal services presents significant opportunities for improving efficiency while raising concerns regarding legal certainty, accountability, and professional responsibility. This study examines the application of the precautionary principle in the use of AI by notaries in Indonesia and proposes a legal regulatory framework that accommodates technological innovation without undermining legal integrity. Employing a normative juridical research method, the study utilizes statutory, conceptual, and comparative approaches by analyzing Indonesian legislation alongside international instruments, including the European Union AI Act, the OECD AI Principles, and the UNESCO Recommendation on the Ethics of Artificial Intelligence. The findings indicate that AI should function solely as a decision-support tool under the full supervision of notaries. The study proposes five normative parameters—verification, human oversight, confidentiality, accountability, and transparency—as minimum standards for AI governance in notarial practice, ensuring legal certainty, authentic deeds, public trust, and responsible technological innovation.